Split-bolus vs. multiphasic contrast bolus protocol in patients with pancreatic cancer or cholangiocarcinoma. Issue 119 (October 2019) - Muenzfeld, Hanna; Mahjoub, Samy; Roehle, Robert; Pelzer, Uwe; Bahra, Marcus; Boening, Georg; Hamm, Bernd; Geisel, Dominik; Auer, Timo Alexander
Highlights: Split bolus protocols may be suitable for pancreatic- and cholangiocarcinoma. The split bolus protocol provides sufficient levels of diagnostic accuracy. Split bolus protocol is equal to the multiphase protocol regarding image quality. The split bolus protocol lowers the radiation exposure significantly. Split bolus protocols in computed tomography are easy and safe to perform. Abstract: Purpose: To investigate the image quality, diagnostic accuracy, and dose reduction potential of a split-bolus protocol(SBP) compared with a multiphasic protocol(MPP) in the detection of recurrent or progressive pancreatic ductal adenocarcinoma(PDAC) or cholangiocarcinoma(CC) using contrast- enhanced computed tomography(CECT). Materials and Methods: This prospective study included 56 patients who underwent CECT, 28 with our institutional standard MPP(100 ml contrast bolus) and 28 with a novel SBP(110 ml). Radiation exposure was determined in terms of total dose- length product(DLP) and computed tomography dose index(CTDI). Image quality was measured objectively by analysis of attenuation in Hounsfield units(HU) in regions of interest(ROIs) and subjectively by two blinded readers using a Likert scale. Diagnostic accuracy and interreader variability were tested. Results: The total DLP of the SBP group(498.1 ± 43.7 mGy*cm) was significantly lower than in the MPP group(1, 092.5 ± 106.9 mGy*cm; p < 0.001). The SBP showed higher contrast enhancement of all critical anatomical structures including portal vein, liver, and pancreas compared with the MPP, except for the aorta(SBP: 326.9 ± 15.7 HU vs. MPP: 246.7 ± 12.2 HU; p < 0.001). Subjective analysis revealed poorer image quality ratings for important landmarks with the MPP (resection surface: p = 0.624, portal vein: p = 0.395, liver p = 0.361). The two blinded readers correlated significantly. Sensitivity, specificity, positive and negative predictive values (PPV/NPV), and overall interreader variabilities correlated significantly. Furthermore, significantly fewer slices per exam were required for the SBP(1, 823 vs. 3, 235; p < 0.001). Conclusion: The SBP provides the same image quality and diagnostic accuracy as an MPP while significantly lowering radiation exposure in CT follow-up of PDAC or CC.